2019
DOI: 10.4315/0362-028x.jfp-18-044
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Cold Chains for Chesapeake Bay Farmed Oysters and Modeled Growth of Vibrio parahaemolyticus

Abstract: Temperature-controlled supply chains (cold chains) require an unbroken chain of refrigeration to maintain product quality and safety. This study investigated cold chains for farmed oysters raised in the Chesapeake Bay, one of the largest shellfish-growing regions in the United States, and sold live to the half-shell market in surrounding states. Temperature sensors were used in boxes of oysters from February to September 2017, which generated 5,250 h of temperature data. Thirty-nine businesses participated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Numerous cases of gastroenteritis caused by V. parahaemolyticus have been detected and isolated in Spain, Greece, Britain, Denmark and other countries in Europe over the years [ 72 , 73 ]. Love et al [ 74 ] demonstrated that the cold chain was effective in reducing the risk of V. parahaemolyticus in seafood by modeling the effects of temperature on the growth of this bacterium in oysters. Moderate bacterial growth was detected in oysters that had not entered the cold chain, while bacterial growth stopped once they were under refrigeration.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous cases of gastroenteritis caused by V. parahaemolyticus have been detected and isolated in Spain, Greece, Britain, Denmark and other countries in Europe over the years [ 72 , 73 ]. Love et al [ 74 ] demonstrated that the cold chain was effective in reducing the risk of V. parahaemolyticus in seafood by modeling the effects of temperature on the growth of this bacterium in oysters. Moderate bacterial growth was detected in oysters that had not entered the cold chain, while bacterial growth stopped once they were under refrigeration.…”
Section: Discussionmentioning
confidence: 99%
“…Some parts of the cold chain in the study by Love, Lane, et al. (2019) could not maintain temperatures less than 7.28 °C, particularly during the warmer months when Vibrio control plans were in effect. Consequently, the internal temperature of oysters in the cold chain reached 12.5 °C, which is conducive for the multiplication of V. parahaemolyticus (Fernandez‐Piquer et al., 2011; Parveen et al., 2013).…”
Section: Factors Affecting the Accumulation Of V Parahaemolyticus Inmentioning
confidence: 91%
“…Love, Lane, et al. (2019) investigated the performance of cold chains for the Chesapeake Bay farmed oysters in the United States and reported that 19% of shipments had temperatures higher than 10 °C (50 °F) for longer than 1 hr, which exceeded the recommendation of the National Shellfish Sanitation Program (NSSP) in the United States. In another study by Love, Kuehl, et al.…”
Section: Factors Affecting the Accumulation Of V Parahaemolyticus Inmentioning
confidence: 99%
See 2 more Smart Citations